Validation of an algorithm to determine the primary care treatability of emergency department visits - Jeffery, Molly Moore (BMJ Open, 2016)
OBJECTIVES: We propose a new claims-computable measure of the primary care treatability of emergency department (ED) visits and validate it using a nationally representative sample of Medicare data. STUDY DESIGN AND SETTING: This is a validation study using 2011–2012 Medicare claims data for a nationally representative 5% sample of fee-for-service beneficiaries to compare the new measure's performance to the Ballard variant of the Billings algorithm in predicting hospitalisation and death following an ED visit. OUTCOMES: Hospitalisation within 1 day or 1 week of an ED visit; death within 1 week or 1 month of an ED visit. RESULTS: The Minnesota algorithm is a strong predictor of hospitalisations and deaths, with performance similar to or better than the most commonly used existing algorithm to assess the severity of ED visits. The Billings/Ballard algorithm is a better predictor of death within 1 week of an ED visit; this finding is entirely driven by a small number of ED visits where patients appear to have been dead on arrival. CONCLUSIONS: The procedure-based approach of the Minnesota algorithm allows researchers to use the clinical judgement of the ED physician, who saw the patient to determine the likely severity of each visit. The Minnesota algorithm may thus provide a useful tool for investigating ED use in Medicare beneficiaries.